Baropodometric assessment of the podiatric profile of nursing students in clinical settings: a study protocol - Bernardes, Rafael A. (2022)
Introduction: Nursing students are exposed to increased risks of developing foot and ankle disorders due to prolonged standing and walking positions during clinical settings. This can lead to high dropout rates from nursing degree, thus contributing to a future shortage in nursing professionals. This protocol aims to develop a study to understand the influence of prolonged standing and walking positions on nursing students' foot health, and specifically to study the relationship between the podiatric profile (regional force and pressure exerted on the foot) and related signs and symptoms. Methods and Analysis: A prospective observational cohort study will be conducted with 194 nursing students. Participants will be asked to walk through a baropodometric platform before and after a 5-month clinical training session. Assessment will focus on the change in podiatric profile, namely foot posture and foot function, at 5 months, and changes in foot health at 5 months. The study will start in January 2022 and it's expected to end by June 2022. Discussion: The study aims to perform an innovative assessment of nursing students' podiatric profile, which will allow for a comprehensive description of foot/ankle changes and their relationship with prolonged standing and walking contexts. Ethics and Dissemination: The study was approved by The Ethical Committee of the Health Sciences Research Unit: Nursing (UICISA: E), of the Nursing School of Coimbra (ESEnfC), with the approval code nr. P799_07_2021. The study was also recorded in ClinicalTrials.gov on the number NCT05197166. Findings will be used to publish articles in peer-review scientific journals and oral communications and posters at scientific meetings.